If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(x + 6) + 3 = 39 Reorder the terms: -4(6 + x) + 3 = 39 (6 * -4 + x * -4) + 3 = 39 (-24 + -4x) + 3 = 39 Reorder the terms: -24 + 3 + -4x = 39 Combine like terms: -24 + 3 = -21 -21 + -4x = 39 Solving -21 + -4x = 39 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '21' to each side of the equation. -21 + 21 + -4x = 39 + 21 Combine like terms: -21 + 21 = 0 0 + -4x = 39 + 21 -4x = 39 + 21 Combine like terms: 39 + 21 = 60 -4x = 60 Divide each side by '-4'. x = -15 Simplifying x = -15
| 9x^2+9=0 | | 3(-6x+8)=42 | | (2p^2)-4p+1=0 | | 3x^2-12x=-1 | | 1-2x+9=6 | | 3x-40+2x=15 | | Y^2+4y-8x=4 | | 2a-20=5a+6 | | (x*3)+4=(x*2)+7 | | 2(x-7)=6(1.4-x) | | (x*3)4=(x*2)+7 | | x^2-x-13=0 | | x^2+6x-18=0 | | -7r+3t-s-r+s+4t-t+5s-11r=0 | | 57=-19v | | y=2+0.84x-0.04x^2 | | y=-0.04x^2+0.84x+2 | | 8x^2-16x+8=0 | | x^2+16x=-46 | | X=2x^2+4xy-7y^2 | | 8x+12=44 | | 5s^2-17s=-6 | | 5s^2-17s=-16 | | 4n-9=8n+3 | | 5x+49=3 | | 5y+3=108 | | 9x-3(2x-4)=12(x-7) | | 4y-2=17y+24 | | n-16=2n | | 5a+3(a+2)=22 | | 1.9*4.9= | | 9-7x=59-21x |